Increased VCAM-1 Expression in Short Duration, Untreated Juvenile Dermatomyositis Muscle Biopsies is Regulated by miR-126 - Kim, Erin (2012)
OBJECTIVE: To evaluate Juvenile Dermatomyositis (JDM) for duration of untreated disease (DUD) impact on: vascular cell adhesion molecule-1 (VCAM-1) and microRNA (miRNA) expression in muscle biopsy (MBx); soluble VCAM-1 (sVCAM-1) and TNF-α in sera. METHODS: Pediatric controls (n=8) and untreated JDM (n=28) enrolled. Short DUD (n=11, symptoms ≤2 months before MBx); long DUD (n=17, >2 months symptoms). Vascular structures, characterized by immunoflorescence using antibodies against von Willebrand factor (vWF), VCAM-1, and α-smooth muscle actin (SMA), were measured for total area (microns(2)) and intensity (pixels) (SlideBook 4.2). Circulating sVCAM-1 and TNF-α levels (Mesoscale) were determined (JDM [6 short, 8 long DUD], 5 controls). MiR-126 differential expression in JDM MBx ([3 long, 3 short DUD], 2 controls) was detected by Exiqon’s miRCURY microRNA Array, and confirmed (qRT-PCR) in JDM ([5 short, 5 long], 5 controls). RESULTS: Short DUD JDM had higher total positive area (p=0.043) and intensity/high power field, (p=0.015) of VCAM-1 expression than long DUD JDM or controls (p=0.004, p=0.001 respectively). vWF:Ag+ vasculature displayed greater VCAM-1 intensity in short DUD compared to long DUD (p=0.001). Circulating sVCAM-1 and TNF-α were higher in JDM short DUD than controls (p=0.013, p=0.048 respectively). MiR-126, a negative regulator of VCAM-1 expression, was decreased by 3.39 fold, p=0.006 in controls vs. short DUD; for controls vs. long DUD, no significant difference (0.145 fold, p=0.548). CONCLUSION: In short DUD, miR-126 downregulation is associated with increased VCAM-1 in both muscle and blood, suggesting that VCAM-1 plays a critical role early in JDM disease pathophysiology, augmented by TNF-α.